Optimization of amylase reaction through design of experiments(DOE) - Musfafikri, Musa (2010)
The use of starchy biomass as an industrial raw material bring commercial success of amylases, which have potential industrial applications due to the ability to hydrolyze starch to glucose.The implementations of conventioanl method that employ sreening using one factor at a time usually give inaccurate optimum condition. Moreover,this method is time consuming.Thus,this paper aims to apply design of experiment as a tool to optimize reaction.In this work,the two-level full factorial design and response surface methodology with central composite design was used to identify and optimize the significant parameters.The experiments were conducted with the aid of Design Expert Software 7.1.6.The effect of pH, temperature,substrate concentration and enzyme concentration were studied.The result concluded that the optimized value for pH,temperature and substrate concentration were 8.90, 40.76'C and 5.46% (w/v), respectively;with R2 of 81.86%.The experimental design was proven to be tool for optimization process with less number of experiments and more accurate optimum value.